High neutrophil to lymphocyte ratio and low mean platelet volume level in autism spectrum disorders (Annals of Medical Research, 2021)
Aim: A growing number of studies have indicated that ASD is associated with neuro-inflammation. Recent research has indicated that complete blood count (CBC) may be used for assessing inflammatory markers, offering a cheap, simple and reproducible alternative that is also suitable for routine application. In this study, we evaluated complete blood count (CBC) data in children with ASD, aiming to explore associations between ASD and inflammationMaterial and Methods: Patients diagnosed with ASD between 01.01.2018 and 31.08.2019 were included in the study. CBC results of patients from their initial visit to the clinic were analyzed. The control group consisted of children with matching age and gender visiting the clinic for general examination. CBC parameters of both the study and control groups were evaluated statistically. Results: 67 children diagnosed with ASD and 67 healthy children were included in the study. In the ASD group, the neutrophil/lymphocyte ratio (NLR) was significantly higher than in the control group (p0.001). The cut-off value for NLR was determined as 2.32. The levels of mean platelet volume (MPV) were significantly lower in the ASD group compared to the control group (p0.001). The cut-off value for MPV was determined as 11.75 fl. Conclusion: NLR and MPV measurements, which are simple and readily-available laboratory tests, may serve as important biomarkers for diagnosis of ASD. Increased NLR and lowered MPV levels may be used as screening tools and early intervention predictors for ASD. Further research with a larger sample size may clarify the involvement of inflammation in ASD.
Keywords: Autism spectrum disorder, inflammation, neutrophil/lymphocyte ratio.